Stoichiometry of Carbon, Nitrogen and Phosphorus in Shrub Organs Linked Closely With Mycorrhizal Strategy in Northern China - Yang, Shuang; Shi, Zhaoyong; Zhang, Menghan; Li, Yang; Gao, Jiakai; Wang, Xugang; Liu, Dehong (Frontiers in Plant Science, 2021)
Mycorrhizal strategies include mycorrhizal statuses and mycorrhizal types, which are important reflections of the functional characteristics of ecosystems. The stoichiometry of carbon, nitrogen, and phosphorus in plant organs is an important part of ecosystem functions, which has an important impact on the nutrient cycle of the ecosystem. The concentration of carbon, nitrogen, and phosphorus played a crucial role in ecosystem functioning and dynamics. The purpose of this study is to provide theoretical basis and data support for improving the properties of global terrestrial ecosystems by exploring the impact of mycorrhizal strategies on the stoichiometry of C, N, and P in different shrub organs. In this study, stoichiometric patterns of carbon (C), nitrogen (N) and phosphorus (P) in different shrub organs under different mycorrhizal status or types were analyzed at 725 samples across Northern China. Results showed that in different mycorrhizal status, the highest carbon concentration in shrub organs appeared in the FM mycorrhizal status, and the highest nitrogen concentration appeared in the NM mycorrhizal status. Under different mycorrhizal types, the nitrogen concentration in the shrub organs under the AM mycorrhizal type was the highest, and the phosphorus concentration under the ECM mycorrhizal type was the highest. In the OM or FM mycorrhizal status, the concentrations of C, N, and P in the stems and leaves increase with the increase of the concentrations of C, N, and P in the roots. In the NM mycorrhizal status, the N concentration in the stems and leaves increases with the increase of the N concentration in the roots. Under AM, AM+ECM, ECM mycorrhizal type, the concentrations of C, N, and P are closely related in roots, stems and leaves. The content of plant nutrients in different organs is closely related. It turned out that mycorrhizal statuses or types are able to alter the allocation of C, N and P in different organs, and the relationships of C, N and P among different organs are able to present different trend with the varying of mycorrhizal statuses or types.